1988
DOI: 10.1136/gut.29.12.1628
|View full text |Cite
|
Sign up to set email alerts
|

Altered gastrointestinal immune response in sarcoidosis.

Abstract: SUMMARY Because of the possible clinical association between coeliac disease and sarcoidosis, the incidence of humoral sensitivity to dietary proteins was examined in patients with sarcoidosis. Raised concentrations of circulating IgG antibodies to alpha gliadin were found in 41/99 sarcoid patients whereas antibody levels to casein, beta lactaglobulin and ovalbumen were similar to normal controls. Subsequently, a group of 26 sarcoid patients were selected for small intestinal biopsy; 11 had raised and 15 norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…However, it is higher than would be expected from any population estimates of the prevalence of coeliac disease, notwithstanding the fact that coeliac disease is common in the West of Ireland. In another study of 99 patients with sarcoidosis, positive α-gliadin IgG antibodies were detected in 41%, compared with 5% of normal controls and 93% of patients with coeliac disease 17. No data are available in this study on endomysial or tissue transglutaminase antibody serology.…”
Section: Discussionmentioning
confidence: 64%
“…However, it is higher than would be expected from any population estimates of the prevalence of coeliac disease, notwithstanding the fact that coeliac disease is common in the West of Ireland. In another study of 99 patients with sarcoidosis, positive α-gliadin IgG antibodies were detected in 41%, compared with 5% of normal controls and 93% of patients with coeliac disease 17. No data are available in this study on endomysial or tissue transglutaminase antibody serology.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, in a study of immune reactivity in serum, it was found that nearly 40% of sarcoidosis patients had antibodies to ATP synthase (24%) or to gliadin (15%) (29). Similarly, another study found that approximately 40% of sarcoidosis patients were sensitized to gluten (30). One explanation behind a shared immune reactivity between sarcoidosis and celiac disease could be shared HLA alleles, since DQ2 and DRB1*0301 are strongly linked (31).…”
Section: Figurementioning
confidence: 99%
“…In contrast, a Swedish study by Papadopoulos et al in 1999 found an increased frequency of gliadin antibodies but no actual increase in the diagnosis of celiac disease in patients with sarcoidosis [8]. Similarly, in 1988, McCormick et al discovered elevated levels of gliadin antibodies in Irish patients with sarcoidosis but were not able to diagnose celiac disease by biopsy in a significant number of patients [10]. Despite these studies, there have been several case reports of patients with both diagnoses [16][17][18].…”
Section: Discussionmentioning
confidence: 74%
“…Certain class II haplotypes [8] and gastric autoimmunity [9,10] have been implicated as linking factors. However, there has been no recent literature examining the converse relationship; thus, this study was done to determine the prevalence of sarcoidosis in patients with known celiac disease.…”
Section: Introductionmentioning
confidence: 99%